2015 American Heart Association/American Stroke Association Focused Update of the 2013 Guidelines for the Early Management of Patients With Acute Ischemic Stroke Regarding Endovascular Treatment. Issue 10 (October 2015) - Powers, William J.; Derdeyn, Colin P.; Biller, José; Coffey, Christopher S.; Hoh, Brian L.; Jauch, Edward C.; Johnston, Karen C.; Johnston, S. Claiborne; Khalessi, Alexander A.; Kidwell, Chelsea S.; Meschia, James F.; Ovbiagele, Bruce; et al.
<x xml:space="preserve">Abstract</x> Purpose— The aim of this guideline is to provide a focused update of the current recommendations for the endovascular treatment of acute ischemic stroke. When there is overlap, the recommendations made here supersede those of previous guidelines. Methods— This focused update analyzes results from 8 randomized, clinical trials of endovascular treatment and other relevant data published since 2013. It is not intended to be a complete literature review from the date of the previous guideline publication but rather to include pivotal new evidence that justifies changes in current recommendations. Members of the writing committee were appointed by the American Heart Association/American Stroke Association Stroke Council's Scientific Statement Oversight Committee and the American Heart Association/American Stroke Association Manuscript Oversight Committee. Strict adherence to the American Heart Association conflict of interest policy was maintained throughout the consensus process. Recommendations follow the American Heart Association/American Stroke Association methods of classifying the level of certainty of the treatment effect and the class of evidence. Prerelease review of the draft guideline was performed by 6 expert peer reviewers and by the members of the Stroke Council Scientific Statement Oversight Committee and Stroke Council Leadership Committee. Results— Evidence-based guidelines are presented for the selection of patients with acute ischemic stroke for endovascular treatment, for the endovascular procedure, and for systems of care to facilitate endovascular treatment. Conclusions— Certain endovascular procedures have been demonstrated to provide clinical benefit in selected patients with acute ischemic stroke. Systems of care should be organized to facilitate the delivery of this care.